A better start national science challenge: supporting the future wellbeing of our tamariki E tipu, e rea, mō ngā rā o tō ao: grow tender shoot for the days destined for you - Maessen SE; Taylor BJ; Gillon G; Moewaka Barnes H; Firestone R; Taylor RW; Milne B; Hetrick S; Cargo T; McNeill B; Cutfield W (Taylor and Francis Group, 2023)
The majority of children and young people in Aotearoa New Zealand (NZ) experience good health and wellbeing, but there are key areas where they compare unfavourably to those in other rich countries. However, current measures of wellbeing are critically limited in their suitability to reflect the dynamic, culture-bound, and subjective nature of the concept of ‘wellbeing’. In particular, there is a lack of measurement in primary school-aged children and in ways that incorporate Māori perspectives on wellbeing. A Better Start National Science Challenge work in the areas of Big Data, Healthy Weight, Resilient Teens, and Successful learning demonstrates how research is increasing our understanding of, and our ability to enhance, wellbeing for NZ children. As we look ahead to the future, opportunities to support the wellbeing of NZ young people will be shaped by how we embrace and mitigate against potential harms of new technologies, and our ability to respond to new challenges that arise due to climate change. In order to avoid increasing inequity in who experiences wellbeing in NZ, wellbeing must be monitored in ways that are culturally acceptable, universal, and recognise what makes children flourish.
Keywords: Child wellbeing; healthyweight; successful learning; resilient teens; big data; abetter start national sciencechallenge